The Fifteenth Plaster Festival - Mouzouropoulos, Theseas (My University, 2024)
Poster published in the 15 PLASTER book competition The Fifteenth Plaster Festival brings four exhibitions, three of which are dedicated to graphic design in Latin America and one is related to the international competition. Curated by Xavier Bermúdez (who has been the director of the Mexican Poster Biennale for many years), the The Never Ending Poster exhibition contains nearly one hundred works that illustrate the development of this form of expression in Mexico, mostly in the 21st century. A panorama of what is exceptional and unique in Mexican poster - the blend of tradition and modernity, is revealed through the rich diversity of works that make use of digital interference, drawing and photography. The Cartel Latino show, curated by Elzbieta Chojna, offers an up-to-date review of the creative output of designers from six South American countries. Posters and illustrations from Argentina, Bolivia, Chile, Colum-bia, Uruguay and Venezuela appear to be deeply-rooted in the cultural tradition of the continent on the one hand, while also inspired by European design on the other. These interlacing thoughts and influences are present in the show of the winner of last year's Plaster - Eduardo Davit from Uruguay. More than thirty works revolve around ecology, social issues and cultural events. The global village, or contemporary world, makes it possible for us to keep abreast of social and cultural activities at multiple levels. It takes no effort to immerse oneself in the freely accessible load of information. In this context, the poster is a filter, a suggested interpretation of what is presumed by the artist to matter - we are free to agree with it, to follow it, or to choose an entirely different direction. Importantly, as we are looking at the works created by the participants in the Festival, we are willing to accept the lack of literalness. A separate part of the programme, the international exhibition presents works by the Finalists of the New World competition. Displayed on CoCA's third floor are works that take an original approach to the future or make shrewd comments about the world today. Nearly nine hundred works were submitted from all over the world, offering reflection on the condition of our consciousness. Despite the fact that the motto of the competition was historically inspired and directly referenced the name used in the days of the discovery of both Americas, the works address the future for the most part. The posters help to update our understanding of the world order that is dominated by technology, conflict, artificial intelligence, but also create a vision that is full of hope, a vision of a world of harmony, peace and pure air. Nearly ninety works have been included in the show. The winners of the competition are: Goyen Chen (Taiwan), Justyna Jedrysek (Poland), Daniel Garrow (USA), Jakub Sobezak (Poland), Marco Antonio Cadena Blanco (Bolivia). Honourable mentions were awarded by the Aklen company to Patrycja Matuszewska and Michat Tadeusz Golanski. Krzysztof Biatowicz - curator of the festival
The Future in Now
Keywords: poster design; graphic design